Effectiveness of Psychosocial Intervention on Quality of Life of Mothers of Children with Cancer: A Feasibility Study - Chavan, Seema S.; Mendonca, Theresa L. (Journal of Health and Allied Sciences NU, 2022)
Background Mothers of children with cancer are reported to experience stress more often. For children with cancer, parents are the primary source of social and emotional support, and they are also in charge of how successfully patients manage their illness. The degree of difficulty parents suffer after learning that their child has cancer significantly influences the child's psychological adjustment.Aim The study aimed to assess the effectiveness of psychosocial intervention on quality of life (QoL) among mothers of children with cancer.Materials and Methods Quasi-intervention study design was undertaken, and a purposive sampling technique was used to select the 60 mothers of children with cancer who were assigned randomly to the intervention and control groups. A pretested and validated self-administered questionnaire was used; the sociodemographic, WHOQOL-BREF scale with 26 items was studied.Statistical Analysis Prevalence, demographic pro forma of mother and child was analyzed in terms of frequency, percentage, mean, and standard deviation. Two-factor repeated measures analysis of variance was used to establish the effectiveness of the psychosocial intervention on QoL. Association was done by using the chi-square test. SPSS package was used for analysis.Results Psychosocial intervention was found to be effective in improving QoL scores in psychological health domain (p = 0.02*, p < 0.05), social relationship domain (p = 0.04*, p < 0.05), and environmental health domain (p = 0.001**, p < 0.05). A significant association was found between the physical health domain and information on cancer (p = 0.01*), psychological health domain and financial status (p = 0.03*), social relationship domain and cost of treatment (p = 0.04*), Q1 and Q2 with the place of residence (p = 0.004**, p = 0.02*), and Q2 and financial status (p = 0.03*).Conclusion Mothers of children with cancer undergo a lot of stress and emotional turmoil and are at risk of deteriorating their QoL. Hence, they need to be provided support to address their issues. Thus, health professionals must develop and implement interventions to promote the QoL.
Keywords: psychosocial intervention; cancer; children; mothers; quality of life